Fenomenologia, cognitivismo e teoria musicale (Materiali di Estetica. Terza serie, 2021)
This paper explores the relationships between phenomenology, cognitive sciences, and music theory. West Coast school of phenomenology, by subscribing a Fregean reading of Husserl, interpreted Husserlian philosophy as strictly related to cognitive computationalism (Fodor) and Artificial Intelligence project (Minsky). In his musicological research, David Lewin was involved in this suggestion and modeled mental actions to formalize musical perceptions. The study of phenomenological intentionality and time-consciousness can be useful to improve Lewin’s model. Furthermore, the idea of embodied cognition is noteworthy in order to analyze motor intentionality in musical experiences.
Keywords: Phenomenology of Music; David Lewin; Tonal Intention; Husserl’s Analysis of Time-consciousness; Embodied Music Cognition